(untitled) (Experimental biology, 2015)
This article discusses the role of a point mutation in the etiology of hereditary diseases of cattle, the authors for the detection of genetic defects BLAD, BC, CVM, DUMPS in tribal sires was used polymerase chain reaction and RFLP analysis. Found that domestic breeding bulls are free from harmful genetic mutations.